LEARNING AND TEACHING SYSTEM INNOVATIONS THROUGH GAMIFICATION METHODS IN INCREASING MOTIVATION IN THE NEW-PARADIGM - Puspita, Puspita; Ajahari, Ajahari; Wasliman, Iim; Dianawati, Eva (Proceeding of International Conference on Islamic Education (ICIED), 2022)
The transformation of learning methods from offline to online in the post-pandemic with the new paradigm requires adjustments so that it does not feel boring and motivated. Therefore, strategies such as gamification are needed, namely playing while learning as an effort to innovate the learning process. This study aims to review the role of gamification in increasing learning and teaching motivation. This study uses a qualitative approach to describe the data and facts of the conditions that occur. Data collection was carried out through literature studies in several reputable journals and strengthened by in-depth interviews with students and teachers using the Random Sampling Technique of 56 informants who discussed the application of gamification. The data is coded using the Nvivo 12 application through Word Similarity, then conclusions are drawn using sentiment analysis. This study examines gamification methods, namely points, levels, badges, and leaderboards in increasing motivation, namely cognitive motives, self-expression, and self-enhancement. The results of this study explain that the gamification method can be applied to post-pandemic which overcomes the new paradigm in increasing motivation as an effort to innovate learning and teaching. The gap in this study was that the learning process would be difficult to apply with the same method in changing systems and there was no certainty. This study can provide benefits for students and teachers in the learning and teaching process with a simple and fun method.